Geographic bias in citation rates of conservation research. Issue 3 (27th March 2015) - Meijaard, Erik; Cardillo, Marcel; Meijaard, Emily M.; Possingham, Hugh P.
Abstract: We investigated whether the impact of conservation science is greater for research conducted in countries with more pressing conservation problems. We quantified research impact for 231 countries based on 2 citation metrics (mean cites per paper and h index) and fitted models predicting research impact based on number of threatened bird and mammal species (as a measure of conservation importance of a country) and a range of demographic variables. Citation rates of conservation research increased as a country's conservation need increased and as human population, quality of governance, and wealth increased. Even after accounting for these factors, citation rates among regions and countries within regions varied significantly. The conservation research community needs to consider ways to begin addressing the entrenched disadvantages some countries have when it comes to initiating projects and producing high‐quality research. Abstract : Sesgos Geográficos en las Tasas de Citas de la Investigación para la Conservación Resumen: Investigamos si el impacto de la ciencia de la conservación es mayor para las investigaciones llevadas a cabo en los países con problemas de conservación más apremiantes. Cuantificamos el impacto de la investigación en 231 países con base en dos medidas de citas (promedio de citas por artículo e índice h) y ajustamos modelos para predecir el impacto con base en el número de especies amenazadas de mamíferos y aves (como medida de la importancia de la conservación en un país) y en una gama de variables demográficas. Las tasas de citas de la investigación para la conservación incrementaron conforme incrementó la necesidad de conservación de un país y conforme incrementaron la población humana, la calidad del gobierno y la riqueza. Incluso después de considerar estos factores, las tasas de citas variaron significativamente entre las regiones y los países. La comunidad de la investigación para la conservación necesita considerar formas para comenzar a dirigirse a las desventajas arraigadas que algunos países tienen cuando se trata de iniciar proyectos y producir investigaciones de alta calidad.